(untitled) (World Science, 2025)
The dynamic changes in every aspect of the world around us lead to rapid changes in the professional sphere and people’s lives. Today we are witnessing disappearing professions and those that in a short time become essential for human life and health. Certainly, the profession of "Landscape Architect" can be defined as the profession of the future and, in the context of global climate change, is becoming increasingly important for the survival of humanity, but this also brings with it a number of challenges to the volume and content of the services provided.